# How do you differentiate #f(x)= (2x+1)(2x-3)^3 # using the product rule?

Given:

the Product Rule tells:

Thus:

By signing up, you agree to our Terms of Service and Privacy Policy

To differentiate ( f(x) = (2x + 1)(2x - 3)^3 ) using the product rule, apply the formula ( (uv)' = u'v + uv' ), where ( u = 2x + 1 ) and ( v = (2x - 3)^3 ). Then differentiate each term separately and apply the product rule formula:

( u' = 2 ) (derivative of ( 2x + 1 ) with respect to ( x ))

( v' = 3(2x - 3)^2 \cdot 2 ) (derivative of ( (2x - 3)^3 ) with respect to ( x ))

Now, apply the product rule:

( f'(x) = (2)(2x - 3)^3 + (2x + 1)[3(2x - 3)^2 \cdot 2] )

Simplify the expression:

( f'(x) = 2(2x - 3)^3 + (2x + 1)(6(2x - 3)^2) )

( f'(x) = 2(2x - 3)^3 + 12(2x + 1)(2x - 3)^2 )

So, the derivative of ( f(x) ) with respect to ( x ) is ( f'(x) = 2(2x - 3)^3 + 12(2x + 1)(2x - 3)^2 ).

By signing up, you agree to our Terms of Service and Privacy Policy

To differentiate the function (f(x) = (2x+1)(2x-3)^3) using the product rule, you apply the formula which states that the derivative of the product of two functions is the derivative of the first function times the second function plus the first function times the derivative of the second function.

Let (u(x) = 2x + 1) and (v(x) = (2x - 3)^3).

The derivative of (u(x)) with respect to (x) is (u'(x) = 2), and the derivative of (v(x)) with respect to (x) is (v'(x) = 3(2x - 3)^2 \cdot 2).

Using the product rule formula, the derivative of (f(x)) is:

[f'(x) = u'(x)v(x) + u(x)v'(x)]

Substituting the values:

[f'(x) = 2(2x - 3)^3 + (2x + 1) \cdot 3(2x - 3)^2 \cdot 2]

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7